Language development over the lifespan [ - De Bot, Kees; Schrauf, Robert W. (Routledge, 2009)
Language Development Over the Lifespan is intended as a reference resource for those conducting research on language development and the aging process, and as a supplementary textbook for MA courses in applied linguistics/bilingualism programs (in schools of Education and Liberal Arts) that focus on language attrition/aging and adult literacy development in second languages. It offers an integrative approach to language development that examines changes in language over a lifetime, organized by different theoretical perspectives, which are presented by well-known inte